Molecular Determinants of Sensitivity or Resistance of Cancer Cells Toward Sanguinarine - Saeed, Mohamed E. M.; Mahmoud, Nuha; Sugimoto, Yoshikazu; Efferth, Thomas; Abdel-Aziz, Heba (Frontiers in Pharmacology, 2018)
For decades, natural products represent a significant source of diverse and unique bioactive lead compounds in drug discovery field. In Clinical oncology, complete tumors remission is hampered by the development of drug-resistance. Therefore, development of cytotoxic agents that may overcome drug resistance is urgently needed. Here, the natural benzophenanthridine alkaloid sanguinarine has been studied for its cytotoxic activity against multidrug resistance (MDR) cancer cells. We investigated the role of the ATP-binding cassette (ABC) transporters BCRP/ABCG2, P-glycoprotein/ABCB1 and its close relative ABCB5 in drug resistance. Further drug resistance mechanisms analyzed in this study were the tumor suppressor TP53 and the epidermal growth factor receptor (EGFR). Multidrug resistant cells overexpressing BCRP, ABCB5 and mutated ∆EGFR were not cross-resistant towards sanguinarine. Interestingly, P-gp overexpressing cells were hypersensitive to sanguinarine. Doxorubicin uptake assay carried by flow cytometry revealed that sanguinarine is a potent inhibitor of the P-gp transporter. Moreover, immunoblotting analysis proved that P-gp was downregulated in a dose dependent manner after treating P-gp overexpressing cells with sanguinarine. It was surmised that The inhibition of NFκB activity might explain the collateral sensitivity in CEM/ADR5000 cells. The COMPARE and hierarchical cluster analyses of transcriptome-wide expression profiles of tumor cell lines of the National Cancer Institute identified genes involved in various cellular processes (immune response, inflammation signaling, cell migration and microtubule formation) significantly correlated with log10IC50 values for sanguinarine. In conclusion, sanguinarine may have therapeutic potential for treating multidrug resistant tumors.